Peran Pemerintah Dalam Mengatasi Penyalahgunaan Dana Aspirasi Dan Dampaknya Terhadap Kesejahteraan Masyarakat Di Kabupaten Pati - Denandra, Mayko Raya Rambu; Febriharini, Mahmuda Pancawisma; Prasetyo, Budi (PMIH Untag Semarang, 2025)
This study discusses the strategic role of the government in overcoming the misuse of aspiration funds and its impact on the welfare of the community in Pati Regency. Aspiration funds, which should be used for development and public services, are often misused for personal or certain group interests, thereby hindering equitable development and lowering public trust in the government. Through a qualitative approach with interviews and observations, it was found that the misuse of aspiration funds had a negative impact in the form of financial losses, development inequality, and degradation of public participation. This research highlights the importance of strengthening regulations, harmonizing policies, increasing transparency and accountability, and active community involvement in supervision.Â In addition, innovative solutions such as the implementation of information technology and the establishment of an independent supervisory team are key in creating clean and effective governance of aspiration funds. This research recommends synergy between the government, the community, and supervisory institutions for the realization of accountable public fund management that is in favor of the welfare of the people.